2017
DOI: 10.1080/02640414.2017.1373197
|View full text |Cite
|
Sign up to set email alerts
|

Sex-differences in elite-performance track and field competition from 1983 to 2015

Abstract: The purpose of this study was to assess the veracity of the Court of Arbitration for Sport's assertion that sex-differences in athletic performance in elite-standard track and field competition is of the order of 10-12%. Exponential curves were fitted to the data of selected track and field events of the finals of all IAAF World Championships and Olympic Games from 1983 to 2016. For each curve, the coefficient of determination R was calculated, in combination the corresponding 95% confidence intervals for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The IAAF offered a rare opportunity to Martínez-Patiño to provide oral testimony in the case of the Indian athlete Dutee Chand. The Athletics Federation of India suspended her from taking part in national and international competitions for the reasons set out under the “IAAF Regulations Governing Eligibility of Females with Hyperandrogenism to Compete in Women’s Competition.” Chand lodged an appeal with the Court of Arbitration for Sport (CAS) against the Athletics Federation of India and the International Association of Athletics Federations (IAAF) (Ospina Betancurt et al, 2018 ).…”
Section: Dutee Chand’s Case Martinez-patiño’s Witness Statement and Caster Semenya’s Casementioning
confidence: 99%
“…The IAAF offered a rare opportunity to Martínez-Patiño to provide oral testimony in the case of the Indian athlete Dutee Chand. The Athletics Federation of India suspended her from taking part in national and international competitions for the reasons set out under the “IAAF Regulations Governing Eligibility of Females with Hyperandrogenism to Compete in Women’s Competition.” Chand lodged an appeal with the Court of Arbitration for Sport (CAS) against the Athletics Federation of India and the International Association of Athletics Federations (IAAF) (Ospina Betancurt et al, 2018 ).…”
Section: Dutee Chand’s Case Martinez-patiño’s Witness Statement and Caster Semenya’s Casementioning
confidence: 99%
“…Differences in performances between men and women in Athletics has been extensively examined [ 13 ]. Both longitudinal evaluations [ 14 ] of gender-based performance differences over long time frames and cross-sectional differences in shorter time frames [ 15 ] have been conducted for events in Athletics. Long term studies have indicated that gender differences have been persistent in both differences in absolute performance (e.g., running times, distances jumped) and modeled power production [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long term studies have indicated that gender differences have been persistent in both differences in absolute performance (e.g., running times, distances jumped) and modeled power production [ 14 ]. In the horizontal jumps, differences between men’s and women’s performances have been found to range between 17 and 20% in the long jump and 15 and 18% in the triple jump in the years from 1983 to 2015 depending on the curve fitting approach used [ 15 ]. These approaches have not looked at the differences in relative performance of athletes compared to top performances.…”
Section: Introductionmentioning
confidence: 99%
“…Peak performance in running and jumping events are almost equal in boys and girls until the age of 12 y, after which there are greater increases in strength and power in boys (Malina et al, 1997; Tonnessen et al, 2015). In general, sex differences in peak performance range between 10 and 12% for running events and 19% for jumping events (Cheuvront, Carter, Deruisseau, & Moffatt, 2005; Ospina‐Betancurt, Zakynthinaki, Martínes‐Patiño, Cordente Martinez, & Rodríguez Fernández, 2018; Seiler, De Koning, & Foster, 2007; Thibault et al, 2010). Differences beyond this age have been attributed to hormone‐dependent and red blood cell mass changes in physiological properties (Goswami, Roy, Dalui, & Bandyopadhyay, 2014; Ospina‐Betancurt & Zakynthinaki, 2020).…”
Section: Introductionmentioning
confidence: 99%